Scleria (Cyperaceae) in the state of Pará, Amazon, Brazil - Schneider,Layla Jamylle Costa (2021)
ABSTRACT The present study analyzes the diversity of Scleria in the state of Pará and presents taxonomic treatments for all recorded species. The analysis was based on extensive herbarium studies (CEN, HBRA, HCJS, HSTM, IAN, IBGE, INPA, MFS, MG, RB, and UB) and field expeditions to several municipalities of the state of Pará. Specimens were identified using relevant literature, protologues, and type specimens available online. We recognize 30 species of Scleria arranged in two subgenera and nine sections. Four species (i.e., Scleria arguta, S. burchellii, S. longigluma, and S. vaginata) represent new records for Pará, and a new species is proposed (i.e., Scleria sp.). An identification key, descriptions, illustrations, and comments on diagnostic characters, geographic distribution and habitat for all species are also provided.